2019
DOI: 10.1017/s0007114519002332
|View full text |Cite
|
Sign up to set email alerts
|

Inulin from Jerusalem artichoke tubers alleviates hyperglycaemia in high-fat-diet-induced diabetes mice through the intestinal microflora improvement

Abstract: The rate of hyperglycaemia in people around the world is increasing at an alarming rate at present, and innovative methods of alleviating hyperglycaemia are needed. The effects of Jerusalem artichoke inulin on hyperglycaemia, liver-related genes and the intestinal microbiota in mice fed a high-fat diet (HFD) and treated with streptozotocin (STZ) to induce hyperglycaemia were investigated. Inulin-treated hyperglycaemic mice had decreased average daily food consumption, body weight, average daily water consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 53 publications
2
16
0
2
Order By: Relevance
“…These include the lowering of inflammation as evidenced by the reduced plasma interleukin (IL)-6, IL-1β, and plasminogen activator inhibitor-1 levels, mostly due to the effect of luteolin [57]. On the other hand, other active ingredients of artichoke extract, such as inulin, have been found to produce body weight reduction alongside hypoglycemic effects in obese animals [58]. Further experiments are required in order to better clarify this additional effect of artichoke derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…These include the lowering of inflammation as evidenced by the reduced plasma interleukin (IL)-6, IL-1β, and plasminogen activator inhibitor-1 levels, mostly due to the effect of luteolin [57]. On the other hand, other active ingredients of artichoke extract, such as inulin, have been found to produce body weight reduction alongside hypoglycemic effects in obese animals [58]. Further experiments are required in order to better clarify this additional effect of artichoke derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States in 2018, the Food and Drug Administration approved inulin as a dietary fiber ingredient used to improve the nutritional value of manufactured food products. Inulin-treated hyperglycemic mice had decreased average daily food consumption, body weight, average daily water consumption and relative liver weight and blood concentrations of TAG, total cholesterol, HDL-cholesterol and fasting blood glucose[ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, animal experiments indicated that these extracts elevate superoxide dismutase, catalase, glutathione, and glutathione peroxidase activities in the liver and lower the contents of malondialdehyde in the liver and plasma . Additionally, artichoke can alleviate diabetes induced by a high-fat diet in mice …”
Section: Introductionmentioning
confidence: 99%